The Role of the WTO in Mediate Dispute Palm Oil Between Indonesia and the European Union - Yana Sylvana; Yohanes Firmansyah; Hanna Wijaya; Michelle Angelika S (International Journal of Social Science and Religion (IJSSR), 2020)
Several major European countries, such as France and Germany, have included CPO in the list of non-environmentally friendly products. Some countries impose additional import duties because CPO is considered as damaging as alcohol. This research is descriptive and uses a normative juridical approach. There are several demands put forward by the European Union for palm oil entering its territory, these demands include the importation of palm oil, either for food or for industrial purposes. Hence, the European Union requires sustainable palm oil production. Besides, the European Union believes that the use of palm oil for fuel production will endanger the sustainability of other foodstuffs, especially for the poor. The European Union's accusation of environmental threats is considered impure as environmental protection. Many argue that the accusation is only a political step by the European Union in anticipating the development of exports of Indonesian CPO products to Europe.